Orbital Interactions in Chemistry. - Albright, Thomas A.; Burdett, Jeremy K., 1947-; Whangbo, Myung-Hwan. (Chicester : Wiley, 2013)
This new edition of a bestselling reference on applied molecular orbital theory covers organic, organometallic, inorganic, and solid state chemistry, demonstrating how common orbital situations arise through the whole chemical spectrum. This latest edition features a new chapter on current concepts in solid state chemistry, examples of recent advances in the field, more detailed information on trends in the periodic table, expanded information on the mechanics of group theory, and a new chapter on metals. An essential reference for chemists in the areas of organic, inorganic, solid state, and.
Chapter 7: Molecular Orbitals and Geometrical Perturbation7.1 Molecular Orbitals of AH2; 7.2 Geometrical Perturbation; 7.3 Walsh Diagrams; 7.4 Jahn-Teller Distortions; 7.4.1 First-Order Jahn-Teller Distortion; 7.4.2 Second-Order Jahn-Teller Distortion; 7.4.3 Three-Center Bonding; 7.5 Bond Orbitals and Photoelectron Spectra Of AH2 Molecules; Problems; References; Chapter 8: State Wavefunctions and State Energies; 8.1 Introduction; 8.2 The Molecular Hamiltonian and State Wavefunctions; 8.3 Fock Operator; 8.4 State Energy; 8.5 Excitation Energy; 8.6 Ionization Potential and Electron Affinity.
Print version record.
Keywords: Molecular orbitals; SCIENCE -- Chemistry -- Computational & Molecular Modeling; Molecular orbitals; Electronic books